Variability of water relations and photosynthesis in Eucryphia cordifolia Cav. (Cunoniaceae) over the range of its latitudinal and altitudinal distribution in Chile - Figueroa, Javier A; Cabrera, Hernán M; Queirolo, Cristina; Hinojosa, Luis F (Tree physiology, 2010)
The aim of this study was to investigate, during the summer of the year 2008, the variation in leaf water and photosynthetic characteristics of Eucryphia cordifolia Cav. (Cunoniaceae) along its broad latitudinal distribution in central south Chile (36° to 42° S). The latitudinal variation in water potential (psi(w)), water potential at saturation (psi pi(sat)), water potential at the turgor lost point (psi pi(tlp)), stomatal density of the leaves, leaf nitrogen concentrations and photosynthetic light response were studied in eight populations. The populations located in the northern region of the distribution of E. cordifolia had the lowest leaf water potential. Osmotic potential at full turgor was highest in the two southernmost populations and gradually decreased towards the northernmost points. Similarly, osmotic potential at zero turgor was the lowest in the northern population. On the contrary, the symplastic water content was lower in the two southernmost populations. The highest net photosynthesis rate was recorded for plants in the populations of intermediate distributions, and it was dependent on the precipitation and temperature gradient. The northern populations, which are subject to the lowest precipitations, showed the lowest stomatal densities, which were tightly linked with stomatal conductance variation. Therefore, the variability of A(max) was independent of stomatal density and conductance, so that the northern populations, subject to environments with less water availability, presented higher photosynthetic water use efficiency. Photosynthesis variations were also not associated with changes in leaf water potential or in nitrogen content in E. cordifolia leaves, which did not show any consistent latitudinal or altitudinal trend. In conclusion, the results support our hypothesis that the leaf water relations, stomatal characteristics and photosynthetic rates of the leaf would vary along its latitudinal gradient, helping to explain the ability of E. cordifolia trees to inhabit a broad latitudinal and altitudinal range throughout the central south Chile.